Impact of needle positioning on ablation success of irreversible electroporation: a unicentric retrospective analysis - Mathy, René Michael; Tinoush, Parham; Florencia, Ricardo Daniel da; Braun, Alexander; Ghamarnejad, Omid; Radeleff, Boris; Kauczor, Hans-Ulrich; Chang, De-Hua (Scientific reports, 2020)
Irreversible electroporation (IRE) is an ablation procedure in which cell death is induced by ultrashort electrical pulses. In this unicentric retrospective study we investigated the influence of needle positioning on ablation success. 15 IREs with residual tumor after ablation, detected in the first follow-up MRI, were included, and compared with 30 successful ablations. Evaluation of needle geometry revealed significantly higher values for needle divergence (NDiv, 7.0° vs. 3.7°, p = 0.02), tumor-center-to-ablation-center distance (TACD, 11.6 vs. 3.2 mm, p < 0.001), tumor-to-needle distance (4.7 vs. 1.9 mm, p = 0.04), and tumor diameter per needle (7.5 vs. 5.9 mm/needle, p = 0.01) in patients with residual tumor. The average number of needles used was higher in the group without residual tumor after ablation (3.1 vs. 2.4, p = 0.04). In many cases with residual tumor, needle depth was too short (2.1 vs. 6.8 mm tumor overlap beyond the most proximal needle tip, p < 0.01). The use of a stereotactic navigation system in 10 cases resulted in a lower NDiv value (2.1° vs. 5.6°, p < 0.01). Thus, correct needle placement seems to be a crucial factor for success and the assistance of a stereotactic navigation system might be helpful. As most important geometrical parameter TACD could be identified. Main reasons for high TACD were insufficient needle depth and a lesion location out of the needle plane.
Gesehen am 25.01.2021